Effects of the IGF-1/PTEN/Akt/FoxO signaling pathway on male reproduction in rats subjected to water immersion and restraint stress - Huang, Pan (Mol Med Rep, 2016)
The aim of the present study was to determine the effects of the insulin-like growth factor 1 (IGF-1)/phosphatase and tensin homologue deleted on chromosome 10 (PTEN)/Akt/forkhead box (FoxO) signaling pathway on male reproduction in rats subjected to water immersion and restraint stress (WRS). Sperm morphology, sperm malformation rate, and serum testosterone concentration were analyzed following WRS. In addition, the expression levels and immunolocalization of IGF-1, PTEN, Akt and FoxO proteins, as well as the rate of cell apoptosis in rat testes, were investigated. The results indicated that sperm malformation rate, serum testosterone concentration, and the number of terminal deoxynucleotidyl transferase dUTP nick end labeling-positive cells were increased in the testes after WRS. Furthermore, IGF-1 and FoxO1 proteins were predominantly localized in the sperm cytoplasm during the late stages of spermatogenesis. FoxO1 protein was also localized in Leydig cell cytoplasm. PTEN and total Akt proteins were predominantly expressed in the cytoplasm of Leydig cells and spermatogonia. PTEN protein was also detected in vascular endothelial cells. In addition, IGF-1, PTEN, Akt1, Akt2, FoxO3 and FoxO4 gene expression levels were upregulated following WRS, and peaked after 7 h of WRS. During the recovery period, the expression levels of these genes gradually returned to normal levels. The present study demonstrated that WRS induced sperm damage in the testes. In addition, the results indicated that the IGF-1/PTEN/Akt/FoxO signaling pathway may serve an anti-stress role in the testes of rats subjected to WRS.